Microbial ecology of sandflies—the correlation between nutrition, Phlebotomus papatasi sandfly development and microbiome - Vaselek, Slavica; Alten, Bulent (Frontiers in Veterinary Science, 2025)
The role and the impact of the microbial component on the biology, ecology, and development of sandflies is largely unknown. We evaluated the impact of larval nutrition on laboratory-reared sandflies in correlation to the abundance of food, light starvation, and food with/without live microbiome, by monitoring the survival and development of immature stages, and the longevity of adult sandflies. Within this study we examined 360 larvae, 116 pupae, and 120 adult flies of Phlebotomus papatasi for the microbial gut content. The data showed that the presence of a live and diverse microbiome plays a role in the development and survival of larvae. The mortality rate of the larvae was higher, and larval development was longer for sandflies maintained on microbiome-depleted medium, in comparison to the larvae fed with medium containing alive and complex microbiome. Actively feeding larvae reduce microbial abundance and diversity of the medium. The microbial content of the larval gut depends on the composition of the rearing medium, indicating a potential attraction to certain bacteria. The microbial content of the pupa gut was severely diminished, with overall survival of two bacterial species in adult insects - Ochrobactrum intermedium (found in 95% of dissected adults) and Bacillus subtilis (16%). Further microbial studies may aid in developing biological control methods for sandfly larval or adult stages.